Sosialisasi Peduli Lingkungan: Upaya Menanamkan Pentingnya Menjaga Kebersihan di SD No. 2 Ungasan - Rita Rahayu, Ni Putu Ayu (Sevanam: Jurnal Pengabdian Masyarakat, 2026)
A clean school environment is an important element that supports student comfort and health during the learning process. At SD No. 2 Ungasan, several conditions still exist that indicate the need to strengthen students' understanding of how to maintain environmental cleanliness, especially in terms of sorting waste and disposing of waste properly. In response to this, the Nusantara V KKN Team, Group 25 of I Gusti Bagus Sugriwa State Hindu University, Denpasar, conducted a socialization activity "Let's Create a Clean and Healthy School Environment." This activity was carried out through community education methods that included the delivery of visual materials, interactive discussions, quizzes, video screenings, and sociodramas to strengthen students' understanding. The results of the activity showed that students were able to explain the steps to maintain a clean school environment, recognize the impact of an unmaintained environment, and differentiate between organic, inorganic, and residual waste. Active student participation during the activity demonstrated that the socialization method applied was appropriate to their needs. Overall, this activity made a positive contribution to increasing students' knowledge and awareness of the importance of maintaining a clean environment. Continuous implementation of socialization is recommended so that clean living habits can be further ingrained in the school environment.